2021
DOI: 10.3389/fcvm.2021.648910
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation in Early Stage of Acute Myocardial Infarction Prevent Ventricular Arrhythmias and Cardiac Remodeling

Abstract: Aims: To evaluate whether low level left vagus nerve stimulation (LLVNS) in early stage of myocardial infarction (MI) could effectively prevent ventricular arrhythmias (VAs) and protect cardiac function, and explore the underlying mechanisms.Methods and Results: After undergoing implantable cardioverter defibrillators (ICD) and left cervical vagal stimulators implantation and MI creation, 16 dogs were randomly divided into three groups: the MI (n = 6), MI+LLVNS (n = 5), and sham operation (n = 5) groups. LLVNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Recently, in dogs, mild left VNS without changes in HR has been shown to reduce ventricular arrhythmias and improved left ventricular function. This may be attributed to multiple potential mechanisms including reduced cardiac neuronal sprouting, inhibition of excessive sympathetic nerve sprouting, and reduced pro-inflammatory responses (Zhao et al, 2021 ). The decrease we observed in creatinine levels post-CA with tVNS are in agreement with a prior study which showed that VNS protects against kidney injury induced by ischemia-reperfusion injury through activation of the α7nAChR+ and decreasing pro-inflammatory markers (Inoue et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in dogs, mild left VNS without changes in HR has been shown to reduce ventricular arrhythmias and improved left ventricular function. This may be attributed to multiple potential mechanisms including reduced cardiac neuronal sprouting, inhibition of excessive sympathetic nerve sprouting, and reduced pro-inflammatory responses (Zhao et al, 2021 ). The decrease we observed in creatinine levels post-CA with tVNS are in agreement with a prior study which showed that VNS protects against kidney injury induced by ischemia-reperfusion injury through activation of the α7nAChR+ and decreasing pro-inflammatory markers (Inoue et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vagus nerve stimulation was also shown to decrease infarct size and to halt post-myocardial infarction phenomena such as the remodeling of both the myocytes and the intrinsic cardiac neuronal system. These cardioprotective mechanisms include anti-inflammatory effects, prevention of Connexin 40 and Connexin 43 loss, antioxidative effects, and antiapoptotic effects such as decrease in cytochrome c release and in the proapoptotic Bcl-2-associated X protein levels ( 28 , 89 , 103 106 ). When applied during myocardial reperfusion, VNS was shown to improve ventricular function and reduce arrhythmic episodes via antagonization of the cardiac sympathetic outflow, reduction of reactive oxygen species and of ventricular excitability ( 28 , 103 106 ).…”
Section: Vagus Nerve Stimulation For Cardiovascular Diseasesmentioning
confidence: 99%
“…These cardioprotective mechanisms include anti-inflammatory effects, prevention of Connexin 40 and Connexin 43 loss, antioxidative effects, and antiapoptotic effects such as decrease in cytochrome c release and in the proapoptotic Bcl-2-associated X protein levels ( 28 , 89 , 103 106 ). When applied during myocardial reperfusion, VNS was shown to improve ventricular function and reduce arrhythmic episodes via antagonization of the cardiac sympathetic outflow, reduction of reactive oxygen species and of ventricular excitability ( 28 , 103 106 ). VNS improves left ventricular ejection fraction post-myocardial infarction restoring subcellular levels of calcium-binding proteins (such as SERCA2a, NCX1, and PLB) and can reestablish baroreceptor reflex to the pre-infarction baseline ( 28 ).…”
Section: Vagus Nerve Stimulation For Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other preclinical VNS studies have demonstrated that VNS reduces ventricular arrhythmias and increases ventricular electrical stability in dog and pig models of myocardial infarction (Vaseghi et al, 2017;Nasi-Er et al, 2019). Interestingly, the potential underlying mechanisms identified included suppressing cardiac neuronal sprouting, inhibiting excessive sympathetic nerve sprouting, and pro-inflammatory responses by regulating gene expression (Zhao et al, 2021). Recently, findings from animal studies have suggested that the cardioprotective effects of VNS in myocardial infarction are provided by the activation of the cholinergic anti-inflammatory pathway on cardiac macrophages (Chung et al, 2020).…”
Section: Therapeutic Potential Of Vagal Nerve Stimulation For Cardiov...mentioning
confidence: 99%